Localization policy of selected hotel systems in Cuba under the economic crisis conditions - Rettinger, Renata (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2014)
Each year the meaning of Cuba on the international tourism services market is increasing, which is visible in the size of tourism development and the amount of foreign tourists visiting the country. It was relatively recently that Cuba emerged as an area of tourist reception; prolonged isolation of the country prompted in the early 1990s the need of undertaking a variety of activities aiming at improving the state of the country’s tourist infrastructure, both qualitatively and quantitatively. The case study analyzes the location policies of chosen hotel systems, both foreign (Sol Melia) and Cuban (Cubanacan, Gaviota). One of the main research issues is presenting the spatial expansion of hotels in comparison with the already existing tourism regions, their natural and cultural specification, as well as the ones yet to be developed. Additionally, the analysis of natural, cultural, infrastructural (availability of transportation), economical, and political conditions for the future investments of the hotel industry is also present. It seems valid to state that the most important factor for the development of tourism, especially in the historical sense, was the political one, stemming from the idea of isolating foreign tourists from local inhabitants, which resulted in the emergence of tourist enclaves. In her research, the author concentrates on the problems of tourism development in the Caribbean region. The dominating research topics are the size and spatial differentiation of tourist infrastructure and tourism volume itself together with the directions of the tourism development. The research topics also include the issue of tourist enclaves as a dominating form of tourist infrastructure in the Caribbean region in light of sustainable development and pro-poor tourism.